Role of Dentists in Creating a Tobacco free Society - Amit Vanka; Shanthi Vanka (Archives of Community Medicine and Public Health - Peertechz Publications, 2016)
"Giving up smoking is easy I have done it a thousand times" is an adage that puts in perspective the difficulties in tobacco cessation. Tobacco is a global agent of death [1]. The tobacco epidemic is one of the biggest public health threats the world has ever faced, killing around 6 million people a year. More than 5 million of those deaths are the result of direct tobacco use while more than 600 000 are the result of non-smokers being exposed to second-hand smoke. Nearly 80% of the more than 1 billion smokers worldwide live in low- and middle-income countries, where the burden of tobacco-related illness and death is heaviest [2]. Globally the toll of deaths due to tobacco is on a rise exponentially.